IMPLEMENTATION OF ENERGY LAW OF HYBRID POWER STATION FOR SOCIAL WELFARE - Dyah Ayu Widowati (Fakultas Hukum Universitas Gadjah Mada, 2014)
This study was aimed to investigate the Implementation of Energy Law of Hybrid Power Station for Social Welfare in Pantai Baru. The problem formulations are the management and utilization of hybrid power station in Pantai Baru and implementation of energy law of hybrid power station for social welfare in the fields of economy and information in Pantai Baru. Based on data analysis it is concluded that the management of hybrid power station in Pantai Baru is performed collaboratively between government and the society. The existence of hybrid power station in pantai baru has positive impacts in economy and information. Penelitian ini meneliti Pelaksanaan Hukum Energi Pembangkit Listrik Tenaga Hibrid untuk Kesejahteraan Rakyat di Bidang Ekonomi dan Informasi di Pantai Baru. Masalah yang diteliti adalah bentuk pengelolaan dan pemanfaatan pembangkit listrik tenaga hibrid di Pantai Baru dan pelaksanaan hukum energi pembangkit listrik tenaga hibrid untuk kesejahteraan rakyat di bidang ekonomi dan informasi di Pantai Baru. Berdasarkan analisis data dapat disimpulkan bahwa pengelolaan pembangkit listrik tenaga hibrid yang ada di pantai baru dilakukan secara kolaboratif, antara pemerintah dengan masyarakat. Kehadiran pembangkit listrik tenaga hibrid yang ada di pantai baru telah memberikan dampak positif di bidang ekonomi dan informasi.